2021
DOI: 10.18502/cbj.v1i1.7515
|View full text |Cite
|
Sign up to set email alerts
|

The study of the prevalence of vitamin D3 deficiency and its relationship with blood glucose level after coronary artery bypass graft operation among patients with diabetes

Abstract: Objectives: Nowadays, vitamin D3 (VitD3) deficiency is among the most common dietary deficiencies around the world. Researchers have paid more attention to VitD3 because it is a vital element of the body and has a plausible relationship with various diseases such as diabetes mellitus type II. This study was conducted to examine the prevalence of vitamin D3 deficiency and its relationship with blood sugar levels in people with diabetes undergoing coronary artery bypass grafting (CABG). Methods: An observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These findings were corroborated by a more recent study by [11] which revealed that the main obstacles to blood donation were medical reasons (32%). It is also supported by one study conducted in the United State of America showed that the lack of a convenient location was the most important factor for both first time (42%) and repeat donors (43%), this "convenience factor" was much more important to donors who were age 25 or younger [15] [36] [37]. Out of 67 majorities of participants with 35(62%) refused once while only 4(6%) refused more than 3 times.…”
Section: The Factors That Discourage Voluntary Donation Of Bloodmentioning
confidence: 88%
“…These findings were corroborated by a more recent study by [11] which revealed that the main obstacles to blood donation were medical reasons (32%). It is also supported by one study conducted in the United State of America showed that the lack of a convenient location was the most important factor for both first time (42%) and repeat donors (43%), this "convenience factor" was much more important to donors who were age 25 or younger [15] [36] [37]. Out of 67 majorities of participants with 35(62%) refused once while only 4(6%) refused more than 3 times.…”
Section: The Factors That Discourage Voluntary Donation Of Bloodmentioning
confidence: 88%